Distribution of Copper Electrochemical Nucleation Activities on Glassy Carbon: A New Perspective Based on Local Electrochemistry. Issue 10 (1st October 2022) - Torres, Daniel; Bernal, Miguel; Demaude, Annaëlle; Hussain, Sajid; Bar, Laure; Losada-Pérez, Patricia; Reniers, François; Ustarroz, Jon
Abstract : The electrochemical nucleation and growth (EN&G) on active surface sites has been a concept of fundamental and technological interest for several decades. Here, we have studied the EN&G of Cu on glassy carbon with a new perspective using the Scanning Electrochemical Cell Microscopy (SECCM), in combination with scanning electron microscopy, atomic force microscopy, and X‐ray photo-electron spectroscopy. Unlike the conventional macroscopic approach, we leveraged the spatial resolution of the SECCM to probe individual sites on the same surface, independently from each other, revealing regions with different energy barriers for nucleation and a distribution of activities for EN&G at the microscopic scale. This site-dependent activity can be modified with common surface pretreatments (i.e., polishing and preanodization). We addressed the electrochemical diversity through multiple descriptors and used them to conduct statistical analysis, supported by surface characterization techniques, bringing forward information that is simply unavailable with the conventional macroscopic approach. This work serves as a departure point to conceive new analysis strategies and address the real nature of active sites for nucleation.